The application of 50g oral glucose challenge test in screening for gestational diabetes mellitus in patients attending antenatal care OPD - Rajput, Disha Andhiwal; Gedam, Jaya Kundan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To screen patients at average risk for Gestational Diabetes using 50g Glucose Challenge test, to ascertain the prevalence of Gestational diabetes through further diagnostic testing and to prevent and manage complications. Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance of variable severity with onset or first recognition during pregnancy. Women with GDM are at risk for maternal and foetal complications, so it is important to screen all the pregnant woman. Methods: This study was conducted in 198 patients between 24 and 28 weeks of gestation, attending the Antenatal clinic. 50g oral glucose is administered irrespective of time of the last meal and plasma glucose is measured one hour later. Patients with plasma glucose levels more than 140 mg/dl were subjected to a 100g oral glucose tolerance test, patients with two or more abnormal reading were labelled as GDM and managed accordingly. Results: Prevalence of GDM in our study was 9.59%. Maternal complications like gestational hypertension, vaginal infections and foetal complications were much higher in GDM patients as compare to non GDM group. Conclusions: GDM is a disease which adversely affects both mother as well as foetus. It is concluded that 50 gm glucose challenge test at 24-28 weeks of gestation with a cut-off value of 140 mg/dl is a reliable screening test for GDM. This test offers the best combination of ease and economy of use and reproducibility in screening for gestational diabetes mellitus in average risk patients.